A Mixed-Methods Evaluation of a Community-Based Glaucoma Check Service in Hackney, London, UK. (4th July 2017) - Holdsworth, Elizabeth; Datta, Jessica; Marks, Dalya; Kuper, Hannah; Lee, Helen; Leamon, Shaun; Lindfield, Robert; Wormald, Richard; Clarke, Jonathan; Elkarmouty, Ahmed; Macdowall, Wendy
ABSTRACT: Purpose : To evaluate the uptake, feasibility and acceptability of a general practice-based optometrist-led glaucoma check service. The service targeted people of black Caribbean and black African descent aged 40–65 years, resident in Hackney, London, United Kingdom. Methods : The study used a mixed-method design, including analysis of service data, prospective audit of secondary care referrals patient survey, cost-consequence analysis, and interviews with staff involved in developing and implementing the service. Results : A total of 3040 patients were invited to undergo the free check; 595 (19.6%) booked an appointment and 461 (15.2%) attended. Overall, 31 patients (6.8%) were referred to secondary care, of whom 22 attended and were assessed for glaucoma. Four were diagnosed with glaucoma and eight with suspected glaucoma, i.e. 2.6% of patients who underwent the check. The cost per patient identified with suspected or confirmed glaucoma was £9, 013. Staff who were interviewed suggested that patients who attended might be those who routinely attended optometrist appointments, however only 62.4% of survey respondents reported having had an eye examination in the previous two years, and 11.4% of women and 16.0% of men reported never having had an eye examination. Conclusion : This study represents one possible configuration for a glaucoma case-finding service, and it contributes to a wider debate about whether screening, targeted or otherwise, should be offered in the UK. Our findings suggest that general practice is an acceptable setting and that such a service may reach some people not previously engaged with primary eye care services.